Highly Enantioselective Bromocyclization of Tryptamines and Its Application in the Synthesis of (−)‐Chimonanthine1. Issue 49 (10th October 2013) - Xie, Weiqing; Jiang, Guangde; Liu, Huan; Hu, Jiadong; Pan, Xixian; Zhang, Hui; Wan, Xiaolong; Lai, Yisheng; Ma, Dawei
<x xml:space="preserve">Abstract</x> A shorter path: A highly enantioselective bromocyclization of tryptamine has been developed using an anionic chiral phase‐transfer catalyst. This method provides a direct approach for preparing chiral 3‐bromopyrroloindoline from tryptamine, which enables a four‐step enantioselective synthesis of (−)‐chimonanthine. PG=protecting group.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>